Extraordinary role of Zn in enhancing thermoelectric performance of Ga-doped n-type PbTe - Luo, Zhong-Zhen (2022)
Although Ga doping can weaken the electron phonon coupling of n-type PbTe, Ga-doped PbTe has a relatively low carrier concentration (n) and high lattice thermal conductivity (κlat), resulting in a lower figure of merit (ZT) compared with those of other top-performing n-type PbTe-based thermoelectric materials. Herein, we report the extraordinary role of Zn in enhancing the thermoelectric performance of Ga-doped PbTe. It is discovered that Zn can simultaneously improve the electronic transport properties and decrease the κlat of Ga-doped PbTe, thereby affording a record high ZTavg ~1.26 at 400–873 K, with a maximum ZT value of 1.55 at 723 K. The isoelectronic substitution of Zn for Pb in Ga-doped PbTe increases the electrical conductivity and n by inducing the nucleation and growth of Ga2Te3 in the second phase. The formation of Ga2Te3 results in nonstoichiometric and Te deficiency in the PbTe matrix, which increases the number of electron carriers. Additionally, discordant Zn and Ga atoms with the highest displacement of ~0.35 Å for Zn alloying, as well as Ga2Te3 nanocrystals ranging from 30 to 200 nm coherently embedded into the PbTe matrix effectively weaken the phonon modes and scatter heat-carrying phonons, resulting in a significant reduction in κlat.